Traction Network Protection Based on Similarity of Transient Current Waveform - Chen, Shilong; Zhang, Zihang; Liu, Hao; Bi, Guihong; Xing, Chao; Li, Pengsong; Zhang, Wenying (Frontiers in Energy Research, 2022)
In this paper, a protection scheme for the traction network of the penetrating co-phase traction direct power supply system based on the waveform similarity at both ends of line is proposed. Besides, research on the transmission characteristics of fault current is also carried out. This article, from the perspectives of the reflection and refraction process, attenuation degree, and polarity of fault current, analyzes the correlation and difference of current waveforms at both ends when interior line faults and adjacent line faults emerge. The correlation of waveforms can be proved by cosine similarity after the process of synchronous squeezes wavelet transformation of fault current. The conclusions are as follows: when the interior line faults occur, the sequence, reflection and refraction process, and attenuation degree reaching both ends are roughly the same, the polarity change direction is the same, and the waveform similarity is high; when the adjacent line faults occur, the sequence, reflection and refraction process, and attenuation degree reaching at both ends are greatly different, the polarity change direction is opposite, and the waveform similarity is low. When a protection scheme is based on using cosine similarity, it can quickly and accurately identify internal or external current faults. Simulation results show that the proposed algorithm can meet the requirements of rapidity, selectivity, and reliability and is not affected by transition resistance and fault inception angles, so it has an application prospect to a certain degree.